Semi‐quantitative [11C]PiB and [15O]H2O PET measures of cerebrospinal fluid dynamics discriminate amyloid load but not cognitive status. (31st December 2021) - Minhas, Davneet S; Laymon, Charles M; Lopresti, Brian J; Cohen, Ann D; Tudorascu, Dana L; Mason, Neale S; Lopez, Oscar L.; Villemagne, Victor L; Aizenstein, Howard J; Mathis, Chester A; Klunk, William E
Abstract: Background: Altered interstitial and cerebrospinal fluid (CSF) dynamics have been linked to impaired amyloid clearance in animal models of Alzheimer's disease (AD). Recent dynamic PET studies using tau and amyloid PET tracers [ 18 F]THK5117 and [ 11 C]PiB have sought to quantify CSF dynamics in humans [de Leon 2017, Schubert 2019]. The aim of this work was to examine the relationships between [ 11 C]PiB and [ 15 O]H2 O semi‐quantitative measures of CSF dynamics, efflux and influx, respectively; amyloid load; and cognitive status. Method: Nineteen participants consisting of n=5 cognitively normal (CN; 71.6±8.9 years, 3 female), 9 mild cognitive impairment (MCI; 68.6±9.9 years, 2 female), and 5 Alzheimer's disease (AD; 67.0±9.0 years, 0 female) subjects underwent [ 11 C]PiB PET (0‐90min post‐injection, 34 frames), [ 15 O]H2 O PET (0‐3min post‐injection, 20 frames), and 1.5T T1 MR imaging. MR images were processed using FreeSurfer 7.1 (FS). Amyloid load status (PiB‐/+) was assessed using a FS Global [ 11 C]PiB 50‐70min SUVR (cerebellar gray matter [GM] reference) and a cutoff of 1.35 SUVR. FS lateral ventricle ROIs were eroded using a 5mm kernel to minimize partial volume contamination from neighboring tissue and used to calculate three semi‐quantitative ventricular CSF outcomes: [ 11 C]PiB ventricular SUVR50‐70 (cerebellar GM reference), [ 11 C]PiB ventricular AUC35‐90 (cerebellar GM reference), and [ 15 O]H2 O ventricular influx ratio (IR; 1.0‐3.0min, whole brain reference). Relationships between PET outcomes were assessed using Spearman's correlations, and group differences across cognitive and amyloid statuses were assessed using the Mann‐Whitney U test. Result: Eleven subjects were classified as PiB+ (1/5 CN, 5/9 MCI, 5/5 AD). Both [ 11 C]PiB ventricular outcomes were significantly correlated with [ 15 O]H2 O IR ([ 11 C]PiB SUVR50‐70 p<0.001; [ 11 C]PiB AUC35‐90 p<0.001). In this population, no significant differences were observed across any pair of diagnostic groups for any of the three ventricular outcome measures (Figure 1). However, significant differences were observed between PiB‐ and PiB+ groups across all three ventricular CSF outcomes (Figure 2; [ 11 C]PiB SUVR50‐70 p=0.033; [ 11 C]PiB AUC35‐90 p=0.041; [ 15 O]H2 O IR p=0.001). Conclusion: The results observed in this population suggest CSF dynamics are altered early in the AD pathophysiological spectrum and are associated with amyloid load. In addition, ventricular CSF dynamics measured using [ 15 O]H2 O IR provided greater discriminatory power than [ 11 C]PiB CSF outcomes.